Characterization of Discounting Words as Powerful Factors in Determining the Quality of Cooperation Within a Working Team - Andonovic, Beti; Petkovski, Stanislav (National and University Library of the Republic of Srpska, 2013)
Abstract: Optimal team communication and long-term cooperation depend on several various categories of factors. One of the factors that may point to efficiency decline within the cooperation is the presence of abusive words (labelling) which are named as discounting words by authors. They represent verbal aggression and are type of condensed metaphors that reflect people’s view of the world around them. Since any communication units that disrupt the good teamwork are of a high interest to any quality manager, there is characterization of the discounting words given. There is a certain correlation between the one who gives the discounting words and the one who receives them. There is also a chart of some of the discounting words given and conclusions included.